Individuals’ positive gains from the COVID-19 pandemic: a qualitative study across 30 countries - Li, Jiaying; Davidson, Patricia M.; Fong, Daniel Yee Tak; Li, Yaqin; Lok, Kris Yuet Wan; Wong, Janet Yuen Ha; Ho, Mandy Man; Choi, Edmond Pui Hang; Pandian, Vinciya; Duan, Wenjie; Tarrant, Marie; Lee, Jung Jae; et al. (International Society of Global Health, 2025)
Background Given the limited understanding of individuals’ positive gains, this study aimed to identify these gains that could be leveraged by policymakers to enhance future health and societal resilience. Methods We used a global qualitative approach to survey adults over 18 from 30 countries across six World Health Organization (WHO) regions, who detailed up to three personal positive gains from COVID-19 pandemic via an open-ended question. Inductive thematic analysis was employed to identify main themes, and quantitative methods were used for demographic and regional comparisons based on the percentage of responses for each theme. Results From 35 911 valid responses provided by 13853 participants, six main themes (one negative theme), 39 subthemes, and 673 codes were identified. Five positive gain themes emerged, ordered by response frequency: 1) improved health awareness and practices; 2) strengthened social bonds and trust; 3) multi-dimensional personal growth; 4) resilience and preparedness building; 5) accelerated digital transformation. The percentage of responses under these themes consistently appeared in the same order across various demographic groups and economic development levels. However, there were variations in the predominant theme across WHO regions and countries, with either Theme 1, Theme 2, or Theme 3 having the highest percentage of responses. Although our study primarily focused on positive gains, unexpectedly, 12% of responses (4304) revealed ‘negative gains’, leading to an unforeseen theme: ‘Distrust and emerging vulnerabilities.’ While this deviates from our main topic, we retained it as it provides valuable insights. Notably, these ‘negative gains’ had a higher percentage of responses in areas like Burundi (94.1%), Rwanda (31.8%), Canada (26.9%), and in the African Region (37.7%) and low-income (43.9%) countries, as well as among non-binary individuals, those with lower education, and those facing employment challenges. Conclusions Globally, the identified diverse positive gains guide the domains in which health policies and practices can transform these transient benefits into enduring improvements for a healthier, more resilient society. However, variations in thematic responses across demographics, countries, and regions highlights need for tailored health strategies.